2021
DOI: 10.1080/21645515.2021.1917236
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary evidence on the safety profile of BNT162b2 ( Comirnaty ): new insights from data analysis in EudraVigilance and adverse reaction reports from an Italian health facility

Abstract: The first vaccine against SARS-CoV-2 made available in Italy has been BNT162b2, the two-dose mRNA-based vaccine developed by Pfizer-BioNTech. The ASST Fatebenefratelli-Sacco hospital is located in one of the areas most affected by the pandemic, and to date over 2000 healthcare professionals have been injected with both vaccine doses. We have collected all spontaneous safety reports in which BNT162b2 was designated as the possible cause. We also have carried out a descriptive analysis of reports submitted in Eu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 6 publications
(8 reference statements)
2
15
0
Order By: Relevance
“…We encountered clinically and histologically strikingly different cutaneous adverse reactions in the course of both mRNA-based and viral vector-based COVID-19 vaccines. Some of the described cutaneous ADR appeared later than twenty days after vaccine delivery, and they might be overseen in standard study protocols, accordingly [5,14,15,17]. In the following, we will put our results into perspective with the available literature and outline the current point of view about the occurrence of distinct dermatoses in connection with COVID-19 vaccines.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…We encountered clinically and histologically strikingly different cutaneous adverse reactions in the course of both mRNA-based and viral vector-based COVID-19 vaccines. Some of the described cutaneous ADR appeared later than twenty days after vaccine delivery, and they might be overseen in standard study protocols, accordingly [5,14,15,17]. In the following, we will put our results into perspective with the available literature and outline the current point of view about the occurrence of distinct dermatoses in connection with COVID-19 vaccines.…”
Section: Discussionmentioning
confidence: 91%
“…Vaccines may be considered as specific drugs with the purpose to achieve a protective immune response; hence, they bear class-specific side effects [11]. The newly developed COVID-19 vaccines are no exception, and numerous studies have addressed this topic [12][13][14][15][16][17]. We encountered clinically and histologically strikingly different cutaneous adverse reactions in the course of both mRNA-based and viral vector-based COVID-19 vaccines.…”
Section: Discussionmentioning
confidence: 98%
“…Recently published data obtained from vaccinated healthcare workers in Hong Kong suggested that, compared with Comirnaty, the quantity of antibodies induced in adults receiving CoronaVac is substantially lower [22] . Also, it has been suggested in a meta -analysis that, across different vaccine platforms, there are obvious trade-offs between various qualities of the vaccines including mild reactogenicity and the strength of the triggered immune response [11] . It is possible that the general immune response induced by vaccination was weaker among those receiving CoronaVac, compared with those receiving Comirnaty, and thus potentially a lower risk of adverse reactions followed the vaccination of the participants; further immunoepidemiologic studies are needed to test this hypothesis because there is no direct relationship between side effects and protection.…”
Section: Discussionmentioning
confidence: 99%
“…Comirnaty (Pfizer-BioNTech) Covid-19 vaccine utilises mRNA for immunization against Covid-19 [9] , [10] As of July 2021, >100 countries have approved it for emergency use and rolled out massive vaccination programs. From published clinical data [11] , [12] , it is observed that a relatively high proportion of vaccinated individuals reported discomfort or adverse reactions following vaccination [10] , [13] . In a large randomized controlled trial [10] , approximately 80% of vaccinated adults aged 16–55 reported at post-vaccination adverse reactions following both doses (first dose: 83%; second dose: 78%) such as pain at the injection site, fatigue, dizziness, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, some more recent prospective "real-world" studies about ADRs to COVID-19 vaccines included reactions during the first week after vaccination or even only the first three days [22]. Only recently did dermatologists begin to report cutaneous ADRs with adequate distinction to reveal that the vaccines are capable of eliciting very different inflammatory cutaneous reactions [21,23,24]. It is also important to mention that the latency between vaccination and onset of delayed skin reactions may exceed 10 days [25].…”
Section: Vaccine (Developing Institution)mentioning
confidence: 99%